2018
DOI: 10.1371/journal.ppat.1006947
|View full text |Cite
|
Sign up to set email alerts
|

The root-knot nematode effector MiPFN3 disrupts plant actin filaments and promotes parasitism

Abstract: Root-knot nematodes secrete effectors that manipulate their host plant cells so that the nematode can successfully establish feeding sites and complete its lifecycle. The root-knot nematode feeding structures, their “giant cells,” undergo extensive cytoskeletal remodeling. Previous cytological studies have shown the cytoplasmic actin within the feeding sites looks diffuse. In an effort to study root-knot nematode effectors that are involved in giant cell organogenesis, we have identified a nematode effector ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 79 publications
(91 reference statements)
0
30
0
Order By: Relevance
“…Actin reorganization is crucial for the development and expansion of nematode feeding sites. When Mi131, a protein from M. incognita that bears a profilin domain, was expressed in protoplasts in which the actin cytoskeleton had been labeled with GFP, the actin cytoskeleton appeared fragmented ( Leelarasamee, 2015 ). Profilin from the protozoan parasite Toxoplasma gondii plays a role in motility and serves as a microbial ligand that is recognized by the host innate immune system, functioning like bacterial flagellin ( Plattner et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Actin reorganization is crucial for the development and expansion of nematode feeding sites. When Mi131, a protein from M. incognita that bears a profilin domain, was expressed in protoplasts in which the actin cytoskeleton had been labeled with GFP, the actin cytoskeleton appeared fragmented ( Leelarasamee, 2015 ). Profilin from the protozoan parasite Toxoplasma gondii plays a role in motility and serves as a microbial ligand that is recognized by the host innate immune system, functioning like bacterial flagellin ( Plattner et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some other effector proteins can also bind actin monomers to manipulate plant actin in conjunction with the enhancement of the expression of the genes encoding endogenous actin-depolymerizing factor (ADF), as described for MiPFN3 in M. incognita by Leelarasamee et al (2018). Their results suggested that diminishing actin network density was important to facilitate nematode feeding.…”
Section: Role Of Rkn Effector Proteins In Host Plant Defense Responsesmentioning
confidence: 99%
“… Schematic representation of the gene expression patterns of 38 Meloidogyne graminicola genes encoding candidate effectors or homologs of Meloidogyne effectors [ 10 , 11 , 12 , 13 , 14 , 15 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Each row represents a gene and each column represents a stage of nematode development (J2: pre-parasitic J2s, Nip: in susceptible rice plants, Tog: in resistant rice plants) either at 2, 4 or 8 dpi.…”
Section: Figurementioning
confidence: 99%